2015
DOI: 10.1021/acsami.5b04868
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous P(DLLA–CL) Balloons as Calcium Phosphate Cement Filled Containers for Bone Repair: in Vitro and in Vivo Studies

Abstract: The spinal surgeon community has expressed significant interest in applying calcium phosphate cement (CPC) for the treatment of vertebral compression fractures (VCFs) and minimizing its disadvantages, such as its water-induced collapsibility and poor mechanical properties, limiting its clinical use. In this work, novel biodegradable electrospun nanofibrous poly(d,l-lactic acid-ϵ-caprolactone) balloons (ENPBs) were prepared, and the separation, pressure, degradation, and new bone formation behaviors of the ENPB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 58 publications
1
48
0
Order By: Relevance
“…When the pore sizes were small, the permeation rate of buffer solution into the scaffolds was slow, leading the low DRs. These results indicated that the catechol modification could effectively adjust the degradation of the scaffolds to be satisfied with the bone or cartilage regeneration …”
Section: Results and Disscussionmentioning
confidence: 82%
See 1 more Smart Citation
“…When the pore sizes were small, the permeation rate of buffer solution into the scaffolds was slow, leading the low DRs. These results indicated that the catechol modification could effectively adjust the degradation of the scaffolds to be satisfied with the bone or cartilage regeneration …”
Section: Results and Disscussionmentioning
confidence: 82%
“…These results indicated that the catechol modification could effectively adjust the degradation of the scaffolds to be satisfied with the bone or cartilage regeneration. 44,45 In vitro mineralization of scaffolds Cartilage defects involve multiple tissues, including the articular cartilage layers, calcified cartilage and subchondral bone. Therefore, it is necessary to simultaneously induce the regeneration of cartilage and subchondral bone.…”
Section: Degradability Of Scaffoldsmentioning
confidence: 99%
“…In this study, biodegradation behavior of the Alg-DA/QCHA gradient scaffolds was detected in a simulated body fluid (SBF) for five weeks, as shown in Figure 4. 22,29 In vitro biomineralization behavior of Alg-DA/QCHA gradient scaffolds Natural bone is an inorganic-organic complex composed of HA and macromolecular collagen fibers. The bottom layer with high QCHA composition displayed a quicker degradation, compared to the other layers with lower QCHA compositions.…”
Section: Synthesis and Characterization Of Qchamentioning
confidence: 99%
“…[26][27][28][29] In comparison with the Alg scaffolds, HA/Alg composite scaffolds exhibited improved mechanical properties. Hydroxyapatite (HA) has recently drawn more interests, due to its chemical structure similarity to the natural bone tissue, outstanding biocompatibility, and excellent mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new fibrous material such as carbon nanotube fibers and other kinds of functional electrospun nanofibers have been developed and have attracted a lot of attention because of their ultimate mechanical and electronic properties. However, the high costs and growing global concerns for environmental issues have caused researchers from various backgrounds to develop new products based on sustainable and ecofriendly materials .…”
Section: Introductionmentioning
confidence: 99%